(untitled) (Labor and Human Development Law Journal, 2018)
The paper discusses the dynamics of the employment relationship of court hearing’s lawyers hired through a computer application, comparing it with the working relationship between the driver and the Uber company. The research investigates the experience of court hearing’s lawyers and presents the case study of such professionals hired and intermediated by a legal company, approaching the perspective of several social actors involved and judicial decisions of cases in which the recognition of the employment relationship of such professionals is asked, as a way of analyzing this professional category. The issue analyzed concerns the “uberization” phenomenon as applied to audiencist lawyers and the hypothesis of it being a similar situation of the "partner" drivers of Uber. For this, the present study analyzes the phenomena in question and the context of their emergence. It is also argued that the employment relationship of these lawyers, as well as those of the drivers of Uber, is located in the gray area of employment, which causes workers to be unprotected from labor rights, and that most appropriate legal arrangement should be understood and sought for dealing with this issue. KEYWORDS: Algorythm. Lawyers. Uberization.